Fatigue and cognitive impairment in immune thrombocytopenic purpura remain stable over time: short report from a longitudinal study. (23rd May 2019) - Mitchell, Eleanor; Frith, James; Newton, Julia
Summary: Immune thrombocytopenic purpura (ITP) is an autoimmune disorder characterised by low platelet counts and increased bleeding risk. In 2009, two cross‐sectional studies determined that fatigue and cognitive impairment (CI) were common in ITP. Here, we report the results from a longitudinal study of 34 people with ITP. Fatigue severity remained unchanged over 7 years, and CI significantly improved. Future fatigue and CI severity could be predicted using baseline severity scores. These findings may be reassuring for ITP patients, as symptoms remain stable over time. Furthermore, using baseline scores to predict future severity could aid the clinical management of ITP.